Monitoramento terapêutico de cães com infecção natural por Leishmania infantum tratados com marbofloxacina combinada ao alopurinol - NASCIMENTO, Janilene de Oliveira (2023)
The treatment of dogs infected with Leishmania infantum has been a challenge for the veterinarian, because it is an expensive and long-term therapy with limited therapeutic options. Thus, the treatment in canine leishmaniasis requires laboratory monitoring, as clinical and immunological response and parasite load of the dog. The objective of this study was to evaluate the combination of marbofloxacin and allopurinol from a clinical perspective and antibody production profile in therapeutic monitoring for CanL (Canine Leishmaniasis). Twenty-six dogs with positive parasitological diagnosis (amastigotes forms the Leishmania) were divided into two treatment groups: G1 - 15 animals treated with marbofloxacin and allopurinol, and G2 - 11 animals treated with miltefosine only. The dogs were monitored for 6 months with clinical evaluations on days D0, D30, D90, and D180, and quantitative serology was performed only at the beginning and end of treatment. Clinical parameters were classified according to severity on a scale of 0 to 3.The qPCR was based on the amplification of L. infantum kDNA (kinetoplast minicircle). In the first three months, animals in G1 and G2 showed reductions of 86.6% and 45.4%, respectively, in clinical scores. Clinical signs relapsed in 9.1% of G2. At the end of treatment, the mean reduction in clinical scores was 61.3% for G1 and 22.3% for G2. Antibody titers decreased by 93.3% with the use of marbofloxacin and allopurinol, compared to 63.6% using miltefosine alone at the end of treatment. In both groups, dogs with high clinical scores had high antibody titers (D0), and as clinical scores decreased on D180, antibody titers also significantly reduced (H = 19.2506; p = 0.0002). Prior to the start of treatment, the mean number of parasites/μL in the bone marrow was, for G1, 239,267 with a median of 13,792 parasites/μL. In G2, the mean was 965,795.1 parasites/μL with a median of 117.8 parasites/μL. Marbofloxacin with allopurinol proved to be viable for reducing parasite load. Monitoring dogs treated with marbofloxacin and allopurinol for six months allowed us to observe a significant clinical improvement, with clinical cure in 20%. In an attempt to achieve a better therapeutic response, the unprecedented proposal for the combination of marbofloxacin and allopurinol demonstrated a potential protocol for use in dogs with Lcan, mainly in Brazil, as there is only one medication licensed for this, with gastrointestinal effects present. However, new studies may demonstrate a reduction in infectivity in dogs.